Izobraževalni filmi kot del učnega gradiva za ranljive ciljne skupine - Javrh, Petra (AS. Andragoška spoznanja, 2013)
The paper presents theoretical approaches to special, didactically augmented visual and audio study materials for adults. We also define the narrow sense of the concept of an educational film as a wellrounded visual material that is structured didactically and contains inherent educational goals both in its design and application. The use of the word film instead of video is legitimized by fulfilling the condition of being a semantically complete and wellrounded product. In the conclusion, we present the findings obtained in Slovenia through experience and practice in the education of vulnerable groups of adults by employing such didactic materials.
Keywords: audio material; audiobook; audiovisual aid; avdio gradivo; avdiovizualno učno sredstvo; didaktični film; educational film; educational movie; informacijsko-komunikacijska tehnologija; information and communications technology; izobraževalni film; izobraževanje odraslih; learning aids; Lifelong learning; multimedia method; multimedial approach; multimedijska metoda; Slovenia; Slovenija; teaching aid; teaching aids; učila; učni pripomočki; vseživljenjsko učenje